Study of dynamic drag of dislocations in KCI crystals with impurities and different dislocation structure - Petchenko, О.M.; Petchenko, G.О.; Boiko, S.M.; Beketov, O.M. (Вопросы атомной науки и техники, 2021)
The frequency spectra of the dislocation decrement of attenuation Δd(ƒ) on KCl + Ba (10⁻² wt.%) impurity single crystals with residual deformations ε of 0.25; 0.45; 0.75% at T = 300 K were investigated by the pulse method in the frequency range 22.5…232.5 MHz. In the framework of the Granato-Lucke theory, the coefficients of dynamic drag of dislocations Β for crystals with different ε are calculated. It is shown that neither the presence of impurities nor the change of the dislocation structure affects the level of dynamic drag of dislocations.